If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2c = -5c + d Solving 2c = -5c + d Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '5c' to each side of the equation. 2c + 5c = -5c + 5c + d Combine like terms: 2c + 5c = 7c 7c = -5c + 5c + d Combine like terms: -5c + 5c = 0 7c = 0 + d 7c = d Divide each side by '7'. c = 0.1428571429d Simplifying c = 0.1428571429d
| 5(x-2)-6x=3 | | 2c=-5c | | 5x+7(x-22)=-22 | | 12(x+3)=24 | | 2112x^2+2640=-463 | | 3*x^2-14*x-3=0 | | 6+x=127 | | x^3-7*x^2-3*x+3=0 | | -10y+9=9y-10 | | 25y+15-16y=7y+1.5y-9 | | -3(4w-1)=8 | | x^2+2xi+11-16i=0 | | 3(1+4b)-b=-85 | | 5y/9/2y=23 | | 4/1^(1/2)-x^(1/2) | | 5x(6-3x)=12 | | -3x-7x/5=5x-(x3) | | 4x+4(2x+10)=100 | | -7/(7/18) | | -4g=-84 | | (2x/5)-(x/2)=40 | | (3/5)x=-6 | | 14-8w=-130 | | (2x/5)-(x/20)=40 | | 3x+3(4x-20)=75 | | 8h=56 | | 7x(4x+3)=5 | | 9+6x=6x+2+4 | | 4t-t-7=2t-4 | | 5(10-3x)=30 | | 16=-5y | | -37=-7x+5(x-5) |